Experimental investigations of a remote atmospheric pressure plasma by electrical diagnostics and related effects on polymer composite surfaces - Brès, Lucie; Gherardi, Nicolas; Naudé, Nicolas; Rives, Bertrand (European physical journal. Applied physics, 2021)
Surface activation of Carbon Fiber Reinforced Polymers (CFRP) using (Poly-EtherEtherKetone) (PEEK) matrices is required to achieve strong and long-term adherent painting on the composite. Among the different techniques, an industrial atmospheric pressure remote plasma has been used in this work to treat PEEK CFRP surfaces. The characterization of this device by means of electrical diagnostics related to the effect of such post-discharge on the surface modifications is discussed. Firstly, electrical characteristics of the discharge show fairly high currents associated to high voltages which suggest a nonestablished and cold arc. Power consumed by the electrical supply associated to post-discharge length and surface temperatures allowed a better understanding of the industrial device. Secondly, the effects of plasma on surface chemistry and topography are analyzed by water contact angle measurements, X-ray Photoelectron Spectroscopy (XPS) and Atomic Force Microscopy (AFM). Investigations showed that treated surfaces exhibited better hydrophilicity mainly due to an incorporation of oxygen containing groups (up to 8.4% more) under air plasma whereas an increase of the nanoroughness and specific surface is preponderant under nitrogen plasma. Different hydrophilic capabilities of the surface obtained in air and nitrogen gas plasmas highlight a potential optimization of activation performances according to industrial specification.